Multi-omic analysis of the effects of low frequency ventilation during cardiopulmonary bypass surgery. (15th June 2020) - Durham, A.L.; Al Jaaly, E.; Graham, R.; Brook, P.O.; Bae, J.H.; Heesom, K.J.; Postle, A.D.; Lavender, P.; Jazrawi, E.; Reeves, B.; Fiorentino, F.; Mumby, S.; et al.
Abstract: Background: Heart surgery with cardio-pulmonary bypass (CPB) is associated with lung ischemia leading to injury and inflammation. It has been suggested this is a result of the lungs being kept deflated throughout the duration of CPB. Low frequency ventilation (LFV) during CPB has been proposed to reduce lung dysfunction. Methods: We used a semi-biased multi-omic approach to analyse lung biopsies taken before and after CPB from 37 patients undergoing coronary artery bypass surgery randomised to both lungs left collapsed or using LFV for the duration of CPB. We also examined inflammatory and oxidative stress markers from blood samples from the same patients. Results: 30 genes were induced when the lungs were left collapsed and 80 by LFV. Post-surgery 26 genes were significantly higher in the LFV vs. lungs left collapsed, including genes associated with inflammation (e.g. IL6 and IL8) and hypoxia/ischemia (e.g. HIF1A, IER3 and FOS ). Relatively few changes in protein levels were detected, perhaps reflecting the early time point or the importance of post-translational modifications. However, pathway analysis of proteomic data indicated that LFV was associated with increased "cellular component morphogenesis" and a decrease in "blood circulation". Lipidomic analysis did not identify any lipids significantly altered by either intervention. Discussion: Taken together these data indicate the keeping both lungs collapsed during CPB significantly induces lung damage, oxidative stress and inflammation. LFV during CPB increases these deleterious effects, potentially through prolonged surgery time, further decreasing blood flow to the lungs and enhancing hypoxia/ischemia. Highlights: Cardiopulmonary bypass surgery causes systemic and pulmonary inflammation. Surgery increases oxidative stress and hypoxia in the lungs and free iron in the blood. Omics suggest ischemia is the principle driver of inflammation. Unlike animal models lung ventilation during surgery increases inflammation. Ventilation increased ischemia, potentially through increased surgical time.